Intervento Omocromico. (Gravina : Centro di Ricerca per l'Informazione e Sperimentazione Internazionale d'Arte e Agricoltura, 1983)
Addamiano, Natale ; Arlotta, Aldo ; Bachhuber, Elizabeth ; Bauman, Tully ; Berke, Sybille ; Binder, Tilman ; Cardone, Wladimiro ; Carless, Georgina ; Chierici, Consuelo ; Cirignola, Anna ; Corona, Claudio ; De Leonardis, Gelly ; Dibattista, Gemma ; De Lucia, Carlo ; Del Monaco, Bruno ; Di Fabrizia, Mimmo ; Di Gioia, Enzo ; Gadaleta, Ignazio ; Gelao, Lello ; Gläsker, Horst ; Hashimoto, Sohei ; Hoinka, Manfred ; Inzitari, Pasualino ; Krenz, Bruno ; Lerario, Sabino ; Maggiulli, Gianna ; Marini, Annalisa ; Marjanov, Wasa ; Miyata, Shosak ; Natuzzi, Andrea ; nils-udo ; Nunziante, Anna ; Oberbaum, Rivka ; Osterwald, Klaus ; Paloscia, Michele ; Pastore, Gloria ; Pastore, Paolo ; Pomodoro, Nino ; Rihs, Christopher ; Rombouts, Guy ; etc.
Intervento Omocromico, from 12th to 17th September 1983, thanks to the active participation of ethically committed artists, a special event took place, which was later interiorized by the sexual responsability of earth through the passing of months - Homocromic Intervention was recorded on the 12-hectare fallow, parcel 34, at Cafiero in the countryside sorrounding Gravina (Bari), in 1983/84 - a project by Grazia Terribile
boek
Keywords: Terribile, Grazia